2016
DOI: 10.1126/sciadv.1501814
|View full text |Cite
|
Sign up to set email alerts
|

Giant electromechanical coupling of relaxor ferroelectrics controlled by polar nanoregion vibrations

Abstract: Polar nanoregion vibrations control the ultrahigh piezoelectric response of relaxor-based ferroelectrics used in applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(73 citation statements)
references
References 48 publications
2
70
0
1
Order By: Relevance
“…These factors lead to a unique characteristic of relaxor-based ferroelectrics in contrast to classical ferroelectrics, that is, the presence of polar nanoregions (PNRs)1718192021, which are believed to be responsible for the high dielectric properties of relaxors171822. Therefore, there have been numerous studies to understand the relationship between the high piezoelectric properties and PNRs in relaxor–PT systems2324252627. For example, Xu et al 23.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These factors lead to a unique characteristic of relaxor-based ferroelectrics in contrast to classical ferroelectrics, that is, the presence of polar nanoregions (PNRs)1718192021, which are believed to be responsible for the high dielectric properties of relaxors171822. Therefore, there have been numerous studies to understand the relationship between the high piezoelectric properties and PNRs in relaxor–PT systems2324252627. For example, Xu et al 23.…”
mentioning
confidence: 99%
“…For example, Xu et al 23. proposed that the softening of the transverse acoustic mode was due to the existence of PNRs, while Manley et al 24. further demonstrated that aligning PNR vibrational modes by a poling electric field can enhance the phonon softening.…”
mentioning
confidence: 99%
“…Great strides in piezoelectric and pyroelectric performances were achieved in 1952, as the lead zirconate titanate (PZT) system of ferroelectrics with favorable piezoelectric and pyroelectric characteristics were developed along with the establishment of their phase diagram . Then, lead magnesium niobate–lead titanate (PMN‐PT) and lead zinc niobate (PZN) relaxors were reported . Thereafter, the rapid development of these inorganic ferroelectric materials, including single crystals, bulk ceramics, and ceramic and single‐crystal thin films, boosted their application in mechanical–electrical transducers, force and temperature sensors, infrared detectors, and energy harvesters .…”
Section: Ferroelectricity and Ferroelectric Materialsmentioning
confidence: 99%
“…Note that very recently in ferroelectric materials, it has been reported that the polar nano-domain alignment makes a major contribution to the ultrahigh piezoelectricity of Pb(Mg 1/ 3 Nb 2/3 )O 3 -PbTiO 3 (PMN-PT). 40,41 Another well-known application of ferroic crystals is actuators which output strain in response to electric field or mechanical stress. However, a severe problem of ferroelectric electrostrictive materials or shape memory materials is the large hysteresis due to the switching of large ferroic domains or first-order ferroic transition, thereby limiting applications needing high precision and a high fatigue life.…”
Section: Ferroic Glass and Its Unusual Propertiesmentioning
confidence: 99%